Interseeding of ruzigrass into soybean: Strategies to improve forage cultivation in no-till systems - Volf, Marcelo R. [UNESP]; Crusciol, Carlos A.C. [UNESP]; Custódio, Ceci C.; Bossolani, João W. [UNESP]; Machado, Fellipe G.; Wruck, Flavio J.; Costa, Claudio H.M.; Ribeiro, Janderson F.; Silva, Leonardo S. (Elsevier, 2021)
No-till (NT) farming is a major soil conservation strategy. In the Brazilian Cerrado, soybean is the main grain crop, and strategies that improve the cultivation of cover crops in the off-season in succession to soybean could facilitate NT for large cultivated areas. In the municipality of Nova Xavantina, MT, Brazil, three experiments were carried out in a randomized block design with four replications. This work aimed to evaluate the establishment of Urochloa ruziziensis (ruzigrass) in succession to soybean as a function of ruzigrass seed treatment, sowing density and phenological stage, and soybean cultivar allelopathic potential. In the first experiment, treatment of ruzigrass seeds with six doses (0, 150, 300, 450, 600 and 750 mL of commercial product 100 kg−1 of seeds) of fipronil + thiophanate-methyl + pyraclostrobin was evaluated. In the second experiment, two ruzigrass interseeding periods (soybean phenological stages R5.5 and R7) and five ruzigrass seed densities (4.3, 6.4, 8.6, 10.7 and 12.9 kg ha−1 VPS) were tested. In the third experiment, the interference of soybean cultivars in the establishment of ruzigrass and the potential allelopathic effect of the cultivars on forage germination were evaluated, six soybean cultivars RR (Roundup Ready®) were used: P98Y70; TMG 115; TMG 132; M 8527; P98Y11; TMG 123. Our results showed that seed treatment facilitated forage establishment in the interseeding system, and the use of high sowing rates at phenological stage R5.5 of soybean promoted greater ruzigrass plant development. The effects of the soybean cultivars on ruzigrass germination varied, suggesting allelopathic effects of the deposition of petioles and soybean leaves on ruzigrass seeds. Thus, an appropriate interseeding strategy can improve forage production in the off-season and favor NT through correct management of forage establishment in succession to soybean.
Keywords: Crop-livestock integration; Second crop, allelopathy; Seed treatment; Urochloa ruziziensis